An integrated model for explaining household recycling behavioural intention - Khalil, Muhammad Salisu (2018)
Globally, municipal solid waste generation is increasing rapidly and its management is becoming more challenging. Kano metropolis faces numerous challenges concerning solid waste management. Although more than 63% of the solid waste generated comes from households, less than 2% of the waste generated is recycled due to low public participation. Consequently, improper disposal of solid waste without proper segregation and recycling causes littering of the city and blockage of drainages, which leads to occurrence of flooding during rainy season. This explains the annual outbreak of diseases such as cholera and malaria fever during the rainy seasons and, the disgusting odour from the city areas where the waste accumulates and decays. Recycling has been proposed as a key strategy through which a sustainable solid waste management can be achieved due to its environmental and economic benefits. However, low public participation has posed a serious challenge to the recycling program. Previous studies and government’s recycling policies focused on top-down approach, neglecting the bottom-up that ensures public involvement. The aim of this study is to develop an integrated model for explaining households’ recycling behavioural intention, using inductive theory building approach (ITB). Data collected from Kano metropolis Nigeria were used to test the integrated model. A multi-stage stratified sampling technique was used to select 393 participants for this study. The proposed integrated model was tested using statistical analysis including descriptive, t-Test, and correlational analyses, and structural equation modeling (SEM). The findings of the descriptive analysis revealed that majority of the respondents have high attitude and intention towards recycling, which is reflected in the high mean scores for recycling intention and attitude (Mean = 4.03) and (Mean = 4.09) respectively. Similarly, the result of the independent t-test shows that there is significant difference in the attitude and intention mean scores between high and low income households. The analysis of the structural equation model indicated that the integrated model accounted for 53% of variance in recycling intention, with attitude having the highest contribution on recycling intention (β = 0.479, p = 0.000). Only Perceived behavioural control was found to have insignificant effect on recycling intention (β = .006, p = 0.907), whereas perceived lack of facilitating conditions shows significant negative effect on recycling intention (β = -.170, p=0.010). The result of the moderating analysis reveals that the relationships between attitude—recycling intention [low income (β = 1.019, p = 0.000) and high income (β = -0.160, p = 0.606)], personal norms— recycling intention [low income (β = 0.127, p = 0.028) and high income (β = 0.406, p = 0.129)], and perceived lack of facilitating conditions—recycling intention [low income (β = 0.089, p = 0.048) and high income (β = -0.499, p = 0.003)] were moderated by income level. Generally, the results in this research indicated that in Kano metropolis low income households are more likely to participate in recycling for their personal gain (financial benefits), whereas, high income households are more likely to participate in recycling when there is availability of facilitating conditions.